2013
DOI: 10.1007/s00296-013-2671-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of TNF-alpha blockers on psychometric measures in ankylosing spondylitis patients: a preliminary observation

Abstract: There is a high co-morbidity between chronic inflammatory disorders and depression. Proinflammatory cytokines like TNF-α seem to play a central role in the pathogenesis of these disorders, and its neutralization provides a potent treatment for inflammatory disorders. Few studies showed that TNF-α blockers also caused an improvement in depressive symptoms associated with these chronic inflammatory disorders. To evaluate the effectiveness of TNF-α blockers on symptoms of ankylosing spondylitis (AS), depression, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Very interestingly, there was no significant difference between efficacy group and inefficacy group for Etanercept. Consistent with a previous study [22], biologic agents may have an antidepressant efficacy besides their anti-inflammatory effect that is independent of their clinical effect.…”
Section: Research Articlesupporting
confidence: 89%
See 1 more Smart Citation
“…Very interestingly, there was no significant difference between efficacy group and inefficacy group for Etanercept. Consistent with a previous study [22], biologic agents may have an antidepressant efficacy besides their anti-inflammatory effect that is independent of their clinical effect.…”
Section: Research Articlesupporting
confidence: 89%
“…In this study, AS patients in drug inefficacy group have higher degree disease activity than patients in drug efficacy group while disease activity is suspected to be one of the main risk factors of psychological disorders in patients with AS [12]. In addition, drug inefficacy will increase medical costs for patients with AS, while anxiety and depression are significantly associated with increased medical costs [21,22].…”
Section: Research Articlementioning
confidence: 86%
“…Indeed, TNF-α inhibitors have also been shown to improve depressive symptoms among people with chronic inflammatory disorders [33], though this does not always appear to be the case [34]. More recently, Arisoy and colleagues [35] have shown that patients with ankylosing spondylitis who were treated with TNF-α inhibitors reported a significant decrease in depression which, importantly, was not associated with changes in markers of clinical disease activity. They, and others [36], have suggested that the improvements in depression but not markers of clinical disease activity, provides support for an inflammatory mechanism underpinning the development and maintenance of depression.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, after an anti‐depressant therapy, TNF‐α levels were observed to be decreased to similar levels as the control group. Arisoy et al . suggested that TNF‐α inhibitors appeared to have potential anti‐depressant effects; this appears to be independent from their anti‐inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%